Relief of Cadmium-Induced Intestinal Motility Disorder in Mice by Lactobacillus plantarum CCFM8610 - Liu, Yang; Wu, Jiangping; Xiao, Yue; Liu, Qing; Yu, Leilei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Zhai, Qixiao (Frontiers in Immunology, 2020)
Cadmium (Cd) is a toxic metal inducing a range of adverse effects on organs including liver and kidneys. However, the underlying molecular mechanisms of Cd-induced intestinal toxicity through dietary intake is poorly studied. This study evaluated the toxic effects of Cd on intestinal physiology and confirmed the effectiveness of the protective mechanism of the probiotic Lactobacillus plantarum CCFM8610 against chronic Cd toxicity. After treatment with Cd, the HT-29 cell line was subjected to iTRAQ analysis, which revealed that changes in the proteomic profiles after Cd exposure were related to pathways involved in the stress response and carbohydrate metabolism. The results of an animal trial also indicated that 10 weeks of Cd exposure decreased the fecal water content and contractile response of colonic muscle strips in mice, and delayed the excretion time of the first black feces. L. plantarum CCFM8610 treatment provided protective effects against these Cd-induced intestinal motility dysfunctions by recovering the levels of neurotransmitters, including substance P, acetyl cholinesterase, vasoactive intestinal peptide, 5-hydroxytryptamine, calcitonin gene-related peptide, and nitric oxide, and suppressing the cellular stress response in mice (e.g., the inhibition of mitogen-activated protein kinase pathways). The administration of this probiotic was also observed to reduce Cd levels in the tissues and blood of the mice. Our results suggest a newly identified protective mechanism of probiotics against Cd toxicity that involves the recovery of intestinal motility and increase in fecal cadmium excretion.